“I would rather be hanged than agree with you!”: Collective Memory and the Definition of the Nation in Parliamentary Debates on Immigration - de Saint-Laurent, Constance (Outlines. Critical Practice Studies, 2014)
This paper explores the meaning attributed to the national group as an entry point into how boundaries between the in-group and the out-group are formed. To do so, it focuses on the representation of the past of the group, taken as a symbolic resource able to produce a raison d’être for national groups, and does so within a dialogical framework. Using the transcripts of the French parliamentary debates on immigration from 2006, it proposes a qualitative analysis of collective narratives of the past along three axes: 1) what meaning do they give to the nation, 2) how is such a meaning produced, and 3) how do the stories told by different groups reply or relate to one another. By identifying the main narratives found in the data and how they relate to each other – within and between groups – it proposes to see collective memory as itself the product of symbolisation processes and, therefore, as a cultural tool especially powerful to produce meaning about the present. This paper also argues that collective memory is a situated construction negotiated with – or contested by – others, made possible by the presence of common historical benchmarks to which different meanings may however be attributed. Finally, it proposes to understand “immigration talk” as potentially the product of the identity questions faced by the national group, rather than the other way around.